PENGEMBANGAN DAN OPTIMALISASI UMKM KWT MAJU BERSAMA MELALUI METODE PELATIHAN BERBASIS DIGITAL - Hendra Kurniawan; Anita Dewi Purwati; Supriyadi Supriyadi; Rossa Wulandari; Dina Warsahanda; Antoni Suseno (Institut Informatika dan Bisnis Darmajaya, 2022)
In the era of increasingly rapid technological development, making it easy to innovate and be innovative to be able to develop for the better is no exception for MSMEs. Not a few MSMEs in Indonesia are still lacking in knowledge to develop their businesses with the digital world such as social media or other platforms. MSMEs need training and education on the importance of running a business in the era of very tight competition. The problems faced by MSMEs group of Women Farmers are advancing Together in the village of insight, Tanjung Sari, Lampung Selatan, namely the lack of knowledge and training on business development using digital media such as digital financial management, sales and marketing and innovation in products. The purpose of this community service activity (PKPM) is carried out in groups using training and education methods to MSME players by using a digital basis so that MSMEs can reach a wider market, we provide the training needed for MSME players in advanced kwt Together that produce banana chips, dumpling chips, and semprong cakes in Wawasan Village, Tanjung Sari, South Lampung with members training fish such as marketing through social media, digital-based financial management, and product packaging innovation and the importance of business letters.